2009
DOI: 10.1111/j.1466-8238.2009.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effects of temperature, latitude and local environment on the reproduction of forest herbs

Abstract: Aim : To investigate the effect of temperature, latitude and local environment on the reproductive traits of widespread perennial forest herbs to better understand the potential impacts of rising temperatures on their population dynamics and colonization capacities. Location : Six regions along a latitudinal gradient from France to Sweden. Methods : Within each region, we collected data from three to five populations of up to six species. For each species, several variables were recorded in each region (temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 49 publications
3
61
3
Order By: Relevance
“…Several studies have demonstrated different aspects of inter-population variation in seed production and seed mass, including climatic factors (Murray et al 2004;Poncet et al 2009), altitudinal gradients (Totland and Birks 1996;Pluess et al 2005), latitudinal variation (Winn and Gross 1993;Garcia et al 2000;Moles and Westoby 2003;Murray et al 2004;Moles et al 2007;De Frenne et al 2009), soil fertility (Wolfe 1995;Tungate et al 2002) and differences in habitat type (Endels et al 2004;Goulart et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated different aspects of inter-population variation in seed production and seed mass, including climatic factors (Murray et al 2004;Poncet et al 2009), altitudinal gradients (Totland and Birks 1996;Pluess et al 2005), latitudinal variation (Winn and Gross 1993;Garcia et al 2000;Moles and Westoby 2003;Murray et al 2004;Moles et al 2007;De Frenne et al 2009), soil fertility (Wolfe 1995;Tungate et al 2002) and differences in habitat type (Endels et al 2004;Goulart et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Resource investment in reproduction, i.e. the product of seed number and seed mass, represent an estimate of how many resources are used for sexual reproduction (De Frenne et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Price et al (2004) pointed out, the value of climate change scenarios is not in the forecasts they provide for specific grid cells or geographic locations, but in the possibility of combining the set of continuously varying data that they provide with other spatially referenced factors to produce a rich multidimensional mixture of possible future environments. Given that the species may show differential responses to these factors (De Frene et al 2009), their relative importance for each species should be assessed together with climate before projecting species distribution models to the future. This assessment may be done by producing single-factor models and merging them into combined, and consequently, more balanced models.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive output commonly varies among plant populations, and differences in both abiotic conditions (Willson and Price 1980;Ågren 1988;De Frenne et al 2009;Toräng et al 2010) and intensity of biotic interactions (Schemske and Horvitz 1988;Ehrlén 1995;Morris et al 2007;Ågren et al 2008) may contribute to such variation. Determining the processes governing spatial variation in flower and seed production is important not only because of their influence on plant population dynamics and distributions, but also because determining these processes can lead to a greater understanding of among-population variation in selection regimes, and of interactions with pollinators and herbivores that depend on flowers or seeds as a resource.…”
Section: Introductionmentioning
confidence: 99%